A Cystine-Rich Whey Supplement (Immunocal®) Provides Neuroprotection from Diverse Oxidative Stress-Inducing Agents In Vitro by Preserving Cellular Glutathione. (15th August 2017) - Winter, Aimee N.; Ross, Erika K.; Daliparthi, Vamsi; Sumner, Whitney A.; Kirchhof, Danielle M.; Manning, Evan; Wilkins, Heather M.; Linseman, Daniel A.
Abstract : Oxidative stress is a principal mechanism underlying the pathophysiology of neurodegeneration. Therefore, nutritional enhancement of endogenous antioxidant defenses may represent a viable treatment option. We investigated the neuroprotective properties of a unique whey protein supplement (Immunocal®) that provides an essential precursor (cystine) for synthesis of the endogenous antioxidant, glutathione (GSH). Primary cultures of rat cerebellar granule neurons (CGNs), NSC34 motor neuronal cells, or HT22 hippocampal cells were preincubated in medium containing Immunocal and then subsequently treated with agents known to induce oxidative stress. Immunocal protected CGNs against neurotoxicity induced by the Bcl-2 inhibitor, HA14-1, the nitric oxide donor, sodium nitroprusside, CuCl2, and AlCl3 . Immunocal also significantly reduced NSC34 cell death due to either H2 O2 or glutamate and mitigated toxicity in HT22 cells overexpressing β -amyloid1-42 . The neuroprotective effects of Immunocal were blocked by inhibition of γ -glutamyl-cysteine ligase, demonstrating dependence on de novo GSH synthesis. These findings indicate that sustaining GSH with Immunocal significantly protects neurons against diverse inducers of oxidative stress. Thus, Immunocal is a nutritional supplement worthy of testing in preclinical animal models of neurodegeneration and in future clinical trials of patients afflicted by these diseases.